The ten "hard" questions in pediatric functional constipation - Flora Fedele; Maria Teresa Fioretti; Elena Scarpato; Massimo Martinelli; Caterina Strisciuglio; Erasmo Miele (BMC, 2024)
Abstract Functional constipation is a common problem in childhood and has a great impact on social, physical, and emotional functioning of affected children and their caregivers. No organic cause of the constipation can be found in approximately 95% of children, defining the "so-called" chronic functional constipation. Its prevalence has been reported to range from 0.7 to 29.6%, with a median of 12%. The diagnosis of functional constipation is exclusively clinical based on the pediatric diagnostic Rome criteria for functional gastrointestinal disorders and does not routinely require laboratory and/or radiological investigations. In case of alarm signs and symptoms that may suggest organic diseases, further investigations can be required. The therapeutic management is based on non-pharmacological and pharmacological approaches. Education, demystification of constipation and reward-based toilet training represent the cornerstones of nonpharmacological management. Disimpaction, maintenance treatment and weaning of medication are all elements of pharmacological treatment. Osmotic laxatives, mainly polyethylene glycol (PEG), are considered the first-choice laxative for both disimpaction and maintenance treatment. The aim of this review is to provide pediatric gastroenterologists with a practical tool to support the clinical and therapeutic management of children and adolescents affected by chronic functional constipation.